The Boundaries of Religious Freedom for Christians During the Pandemic - Geng, Yunpeng; YAO, Tianchong; HONG, Xiaomei (Journal of Research for Christianity in China (JRCC), 2025)
The outbreak of the COVID-19 pandemic has profoundly impacted citizens' lives. During the peak of the epidemic, the Chinese government implemented a series of containment and management measures, including city and village lockdowns, home quarantine, and the closure of religious venues. These measures have affected the broader Christian community to varying degrees, particularly imposing restrictive constraints on the freedom of religious activities. During the pandemic, some Christians saw their self-media accounts shut down, further curtailing their freedom of religious expression. This article examines the pandemic's impact on Christians' freedom of religious belief and explores the balance point for exercising this freedom during the crisis.
Keywords: Christians, pandemic, prevention and control measures, freedom of religious belief, restrictions